PERAN PRAKTISI PUBLIC RELATIONS DALAM ORGANISASI-ORGANISASI DI YOGYAKARTA - Rofiq Anwar (An-Nida : Jurnal Komunikasi Islam, 2015)
The practitioner role of public relations is main subject in the study and research of public relations. Based on survey to 60 practitioners of public relations in Yogyakarta, it was obtained the finding that the dichotomy of managerial and technician role no longer occurs fully. Manager in some aspects has involved in working the technician roles. Then, the public relations staff started to involve in managerial role especially in the role of communication facilitator. This becomes an indication that the role of public relations is increasingly important for organization. It is not only for manager of public relations but also for their staff. Keywords: public relations, organization, managerial role, technician role Peran praktisi public relations merupakan bahasan utama dalam studi dan penelitian public relations. Berdasarkan survei terhadap 60 praktisi public relations di Yogyakarta diperoleh temuan bahwa dikotomi peran manajerial dan teknisi tidak lagi berlaku sepenuhnya. Manajer dalam beberapa hal sudah terlibat untuk menjalankan peran-peran teknisi. Sedangkan staf humas sudah mulai terlibat dalam peran manajerial terutama dalam peran fasilitator komunikasi. Hal ini menjadi pertanda bahwa peran public relations semakin penting bagi organisasi, tidak hanya untuk posisi manajer humas tetapi juga untuk staf humas. Kata Kunci: public relations, organisasi, peran manajerial, peran teknisi